Energy use efficiency and cost-benefits analysis of rice cultivation: A study on conventional and alternative methods in Myanmar - Htwe T.; Sinutok S.; Chotikarn P.; Amin N.; Akhtaruzzaman M.; Techato K.; Hossain T. (Elsevier Ltd, 2023)
Cultivation; Seed; Sustainable development; Conventional methods; Cost-benefits analysis; Crop production; Economic parameters; Energy-use efficiency; Environmental benefits; Rice cultivation; System of rice intensifications; Cost benefit analysis; alternative energy; cost-benefit analysis; crop production; cultivation; energy efficiency; energy market; energy use; rice; seeding; sustainability; Myanmar